Association of CYP1A1*2C Variant (Ile464Val Polymorphism) and Some Hematological Parameters with Acute Myeloid Leukemia (AML) and Chronic Myeloid Leukemia (CML) in Erbil-Iraq. - Sumaya Basit Abdullah; Mustafa Saber Al-Attar (Zanco Journal of Pure and Applied Sciences, 2023)
Acute Myeloid Leukemia (AML) and Chronic Myeloid Leukemia (CML) are life-threatening hematological neoplasms characterized by an uncontrolled proliferation of myeloid progenitors. The phase I metabolism response, which metabolizes xenobiotics and endogenous and exogenous DNA-reactive chemical compounds that may cause genotoxicity and raise the risk of AML and CML, is catalyzed by the cytochrome P450 (CYP) enzyme. The current study is aimed to identify the frequency of CYP1A1*2C polymorphism in AML, and CML patients. Also, compare some hematological parameters in AML and CML to determine the role of allele variants as a risk factor for developing leukemia. Blood samples were collected from 100 (50 AML and 50 CML) patients and 30 controls of both sexes at different age groups. Samples were analyzed for the prevalence of CYP1A1*2C polymorphism, and the results showed that Ile/Ile (AA)- Wild, Ile/Val (AG)- Hetero, and Val/Val (GG)- Homo mutant genotypes were not significantly elevated in the AML and CML group compared to the control group. However, statistically significant differences were found between the patient’s group concerning WBC and Hb estimation, and the frequency distribution of AA- genotypes in both AML and CML patients showed a significant difference. Despite the fact that individuals in the different genotypes have the same probability to develop AML and CML. During treatment genotypes for both AML and CML patients should be considered of patients with the GG genotype who have lower WBC and Hb, especially in AML which may increase disease severity.